Effect of competitive status and experience on heart rate variability profiles in collegiate sprint-swimmers - Flatt, A. A.; Hornikel, B.; Nakamura, F. Y.; Esco, M. R. (The Journal of Strength and Conditioning Research, 2022)
Interindividual differences in training history may be a determinant of heart rate variability (HRV) profiles in collegiate sprint-swimmers and may account for differences observed between elite and subelite athletes. We therefore compared HRV profiles among national-level and conference-level sprint-swimmers while accounting for individual swim-training history. Twenty-eight short-distance swimmers (18 men and 10 women) recorded postwaking HRV throughout a 4-week standardized training period. The 4-week mean (M) and coefficient of variation (CV, a marker of daily fluctuation) were calculated for resting heart rate (RHR) and the natural logarithm of the root mean square of successive differences (LnRMSSD). Swimmers were categorized as national-level (n = 12) or conference-level (n = 16) competitors. Years of competitive experience was documented for each individual to index training history. p < 0.05 was considered statistically significant. No sex-related differences were observed for any variables (p > 0.05). LnRMSSDM (effect size [ES] = 0.95), LnRMSSDCV (ES = -1.18), RHRCV (ES = -1.05), and competitive experience (ES = 1.23) differed between status groups (p < 0.05). Accounting for multicollinearity between competitive experience and LnRMSSD variables (p < 0.05), competitive experience remained associated with LnRMSSDM (r = 0.44, p = 0.02). With competitive experience included as a covariate, differences in LnRMSSDM between status groups disappeared (p > 0.05, ES = 0.31). National-level swimmers exhibit higher and more stable LnRMSSD than that of their conference-level teammates throughout standardized training. Differences in trend characteristics were attributed to training age. This information may assist practitioners with interpreting interindividual differences in HRV profiles throughout training periods among a mixed roster of athletes.